Temporal variability of ventilation in the Eurasian Arctic Ocean - Gerke, Lennart; Arck, Yannis; Tanhua, Toste (Journal of geophysical research. Oceans, 2024)
The Arctic Ocean plays an important role in the regulation of the earth's climate system, for instance by storing large amounts of carbon dioxide within its interior. It also plays a critical role in the global thermohaline circulation, transporting water entering from the Atlantic Ocean to the interior and initializing the southward transport of deep waters. Currently, the Arctic Ocean is undergoing rapid changes due to climate warming. The resulting consequences on ventilation patterns, however, are scarce. In this study we present transient tracer (CFC-12 and SF6) measurements, in conjunction with dissolved oxygen concentrations, to asses ventilation and circulation changes in the Eurasian Arctic Ocean over three decades (1991-2021). We constrained transit time distributions of water masses in different areas and quantified temporal variability in ventilation. Specifically, mean ages of intermediate water layers in the Eurasian Arctic Ocean were evaluated, revealing a decrease in ventilation in each of the designated areas from 2005 to 2021. This intermediate layer (250-1,500 m) is dominated by Atlantic Water entering from the Nordic Seas. We also identify a variability in ventilation during the observation period in most regions, as the data from 1991 shows mean ages comparable to those from 2021. Only in the northern Amundsen Basin, where the Arctic Ocean Boundary Current is present at intermediate depths, the ventilation in 1991 is congruent to the one in 2005, increasing thereafter until 2021. This suggests a reduced ventilation and decrease in the strength of the Boundary Current during the last 16 years.